The nature and management of metastatic melanoma after progression on BRAF inhibitors: Effects of extended BRAF inhibition. Issue 20 (1st July 2014) - Chan, Matthew M. K.; Haydu, Lauren E.; Menzies, Alexander M.; Azer, Mary W. F.; Klein, Oliver; Lyle, Megan; Clements, Arthur; Guminski, Alexander; Kefford, Richard F.; Long, Georgina V.
<x xml:space="preserve">Abstract</x> BACKGROUND The v‐raf murine sarcoma viral oncogene homolog B (BRAF) inhibitor (BRAFi) drugs dabrafenib and vemurafenib have high response rates in BRAF‐mutant, metastatic melanoma; however, 50% of patients progress by 7 months. In this study, the authors examined the nature and management of disease progression (PD) on BRAFi treatment, including characteristics and outcomes of patients who received continued BRAFi treatment beyond disease progression (TBP). METHODS Clinicopathologic data at baseline and at the time of PD were collected for all patients with BRAF‐mutant metastatic melanoma who received BRAFi monotherapy within clinical trials between July 2009 and September 2012. Management and survival after PD were examined, including continued BRAFi TBP (>28 days beyond Response Evaluation Criteria in Solid Tumor [RECIST]‐defined PD). RESULTS Ninety‐five of 114 BRAFi‐treated patients had PD. Fifty‐three of those 95 patients (56%) progressed in extracranial sites alone, 18% (17 of 95 patients) progressed in intracranial and extracranial sites simultaneously, and 16% (15 of 95 patients) progressed in intracranial sites alone. Twenty‐nine of the 95 patients (31%) who had PD progressed in a single site or organ, 48% (46 of 95 patients) progressed in existing metastases only, and 18% (17 of 95 patients) had new metastases alone. At the time of PD, 35 of 95 patients (37%) received no subsequent systemic treatment, 20% (19 of 95 patients) changed systemic treatments, and 39% (37 of 95 patients) continued BRAFi TBP for a median of 97 days. BRAFi TBP and known prognostic factors (Eastern Cooperative Oncology Group performance status, lactate dehydrogenase, RECIST sum of the greatest dimensions of target lesions) were associated with overall survival (OS) from the time of PD; however, in multivariable analysis, BRAFi TBP improved OS (hazard ratio, 0.50; 95% confidence interval, 0.27‐0.93; P=.029). CONCLUSIONS Most BRAFi‐treated patients progressed in existing extracranial sites, and 31% progressed in isolated sites. Compared with cessation, continued BRAFi TBP is associated with prolonged OS even after adjusting for potential prognostic factors at PD. Cancer 2014;120:3142–3153. © 2014 American Cancer Society.